Factors contributing to poor Biomedical Waste Management among Health Workers in Katabi Military Hospital in Entebbe District. A Cross-sectional Study. - Masagazi, Edward; Nimwesiga , Gordon (Student’s Journal of Health Research Africa, 2022)
Background: The study aimed at finding out the knowledge, practices, and the effects of poor Biomedical Waste Management among health workers in Katabi Military hospital– Entebbe district. Methodology: A descriptive cross-sectional study design was carried out from August 2021 to March 2022. to assess the factors contributing to poor Biomedical Waste Management among health workers in Katabi Military Hospital. The study site was purposely selected because it was one of the areas having a lot of staff we were targeting. Respondents were interviewed using pre-coded questionnaires designed in English and the collected data was analyzed using SPSS version 20.0 and later presented in form of tables, pie charts, graphs, and text statements. Results: Respondents had some knowledge about any discarded biological products such as used cotton swabs and blood from wards and laboratories being regarded as medical wastes, Practices of health workers about Biomedical Waste Management were; disposing of all kinds of waste into a general bin, not segregating the biomedical waste according to different categories. Conclusion: There is a need to institute deliberate interventions by Katabi hospital to provide clean dust bins and sanitation facilities to ensure the safe disposal of fecal and solid waste. Recommendations: Government and other stakeholders should ensure that the health workers receive training on how to manage biomedical wastes of any form and supplies to be used should be readily available and should be taught how to use them.